Predictors for runaway behavior in adolescents in South Korea: national data from a comprehensive survey of adolescents - Kim, Hyung Ran; Moon, So-Hyun (Frontiers in Psychiatry, 2023)
Background Runaway behavior is reported to impede the growth, mental health development, and social adjustment of adolescents. Exposure to harmful media causes problematic behaviors in adolescents, sometimes inducing them to run away from home. Methods This study examined the factors influencing adolescents’ runaway behavior. Utilizing the data of 11,354 adolescents from the Survey of Media Usage and Harmful Environment among Adolescents, a hierarchical logistic regression analysis was conducted using the SPSS 24.0 program. Results The significant predictors of runaway behavior were the grade of the adolescent, deviant behaviors (drinking, smoking), autonomous control ability, relationship with family, and harmful media (p < 0.001). This regression model explained 13.1% of the variance in runaway behavior. A significant outcome of this study is that harmful media was identified as one of the factors affecting adolescents’ runaway behavior. Adjusted OR and 95% CI of harmful media was 1.23 (1.10–1.38). Conclusion This study showed that individual, family, social factors, and harmful media influence adolescents’ runaway behavior. The results emphasize the importance of health teachers and the need for early intervention programs, for the identification and prevention of risk factors for adolescents’ runaway behavior.